Attraction of migratory inanga (Galaxias maculatus) and koaro (Galaxias brevipinnis) juveniles to adult galaxiid odours - Cindy F. Baker; Brendan J. Hicks (New Zealand Journal of Marine and Freshwater Research, 2003)
The response of migratory galaxiid juveniles, inanga (Galaxias maculatus) and koaro ( G . brevipinnis) , to the odours of adult galaxiids was tested in a two‐choice chamber apparatus. Both conspecific and heterospecific odours were tested. Inanga juveniles were attracted to adult inanga ( G. maculatus) , banded kokopu (G. fasciatus) , and koaro ( G . brevipinnis) odours. However, they were not attracted to odours from common bullies (Gobiomorphus cotidianus) . Koaro juveniles exhibited a species‐specific attraction to adult koaro odours only. These results demonstrate inanga juveniles can discriminate and are attracted to adult galaxiids during their migratory phase, whilst migratory koaro juveniles exhibit a species‐specific attraction to adult odours similar to the pheromonal attraction previously described for juvenile banded kokopu. This strengthens the hypothesis for the use of pheromonal cues in stream and habitat selection by amphid‐romous galaxiids.